2013
DOI: 10.1128/jb.00508-13
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Regulatory Cascades Control Vibrio fluvialis Pathogenesis

Abstract: c Quorum sensing (QS) is a process by which individual bacteria are able to communicate with one another, thereby enabling the population as a whole to coordinate gene regulation and subsequent phenotypic outcomes. Communication is accomplished through production and detection of small molecules in the extracellular milieu. In many bacteria, particularly Vibrio species, multiple QS systems result in multiple signals, as well as cross talk between systems. In this study, we identify two QS systems in the haloph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 43 publications
(59 reference statements)
2
33
0
Order By: Relevance
“…Our previous study demonstrated that VFH contributes to the pathogenicity of V. fluvialis by inducing IL-1β secretion through the activation of the NLRP3 inflammasome (Song et al, 2015). We also showed that quorum sensing in V. fluvialis positively regulates the production of hemolysin and extracellular protease and affects the cytotoxic activity against epithelial tissue cultures (Wang et al, 2013). …”
Section: Introductionmentioning
confidence: 93%
“…Our previous study demonstrated that VFH contributes to the pathogenicity of V. fluvialis by inducing IL-1β secretion through the activation of the NLRP3 inflammasome (Song et al, 2015). We also showed that quorum sensing in V. fluvialis positively regulates the production of hemolysin and extracellular protease and affects the cytotoxic activity against epithelial tissue cultures (Wang et al, 2013). …”
Section: Introductionmentioning
confidence: 93%
“…2 and 3 ). Moreover , all three QS genes of P. pnomenusa RB38 exhibit low sequence similarity (less than 50%) to any previously characterised LuxI/LuxR homologues, namely BpsI (protein ID: AAQ90168.1) ( Song et al, 2005 ); BpsI (protein ID: AAM21707.2) ( Lumjiaktase et al, 2006 ); BmuR (Protein ID: AAK50054.2) ( Yao, Zhou & Lessie, 2002 ); CepR (Protein ID: AAK70347.1) ( Lutter et al, 2001 ); NmuR (Protein ID: AHB23331.1) ( Gao et al, 2014 ); and VfqR (Protein ID: AGE97288.1) ( Wang et al, 2013 ). This suggests that the QS genes of P. pnomenusa RB38 represent a new evolutionary branch of the QS system and can potentially have novel regulatory roles.…”
Section: Resultsmentioning
confidence: 99%
“…SRX397301 ( Lu et al, 2014 ). The Δ vfh was constructed as previously described using allele replacement strategies ( Wang et al, 2013 ). To construct the pUC- vfh , a chromosomal DNA fragment comprising the vfh open reading frame and its promoter sequence was amplified with the primer pair 5′-CGG AAT TCT AAG ATC ATG TCT GAA TGT-3′/5′-CGG GAT CCC GAC TGA GTT CAG CTC TCA C-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Cell-free culture filtrates of V. fluvialis strains are able to evoke distinct cytotoxic and vacuolization effects on HeLa cells ( Chakraborty et al, 2005 ). Quorum sensing in V. fluvialis positively regulates production of an extracellular protease and hemolysin and affects cytotoxic activity against epithelial tissue cultures ( Wang et al, 2013 ). Of note, the V. fluvialis- caused diarrhea with presence of blood is different from cholera.…”
Section: Introductionmentioning
confidence: 99%